1996
DOI: 10.1108/13620439610152142
|View full text |Cite
|
Sign up to set email alerts
|

Graduate careers in the UK: an examination of undergraduates’ perceptions

Abstract: Within the context of increasingly uncertain career prospects for the UK’s recently expanded student population, examines the career‐related perceptions and expectations of UK business studies undergraduates. Presents data relating to career goals, factors influencing career decisions, levels of (and reasons for) optimism/ pessimism, and anticipated strategies for advancement. Also puts forth comparative data on employees’ career strategies. Identifies and discusses response differences between (1) employees a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 6 publications
3
34
0
1
Order By: Relevance
“…Chan ve Simon (2000) çalışanlar arası ilişki ve şirket içi eğitimin, muhasebe öğrencileri açısından en önemli faktörler olduğunu bulmuşlardır. Counsell (1996) öğrencilerin, ailelerinden ve yakın arkadaşlarından edindiği bilgi ve tavsiyelerin mesleklere yönelik düşüncelerini en çok etkileyen faktör olarak bulmuş ve ayrıca en önemli tercih kriteri olarak gelir ön plana çıkmıştır. Grund (2013) işini bırakanlar arasında yaptığı çalışmada gelirin ve iş tipinin önemli olduğu sonucuna ulaşmıştır.…”
Section: Introductionunclassified
“…Chan ve Simon (2000) çalışanlar arası ilişki ve şirket içi eğitimin, muhasebe öğrencileri açısından en önemli faktörler olduğunu bulmuşlardır. Counsell (1996) öğrencilerin, ailelerinden ve yakın arkadaşlarından edindiği bilgi ve tavsiyelerin mesleklere yönelik düşüncelerini en çok etkileyen faktör olarak bulmuş ve ayrıca en önemli tercih kriteri olarak gelir ön plana çıkmıştır. Grund (2013) işini bırakanlar arasında yaptığı çalışmada gelirin ve iş tipinin önemli olduğu sonucuna ulaşmıştır.…”
Section: Introductionunclassified
“…Prior research suggests that individuals with specific and challenging career goals perform more successfully and productively than those without such goals (Greenhaus, 1987, in Counsell, 1996Ribchester and Mitchell, 2004). Findings from a US study determined that more than 80% of the 220,000 incoming college freshmen rated 'finding a better job' as a very important reason for attending college, while only four per cent planned to seek career guidance and advice to help them make more informed decisions (Orndorff, 2002).…”
Section: Career Goalsmentioning
confidence: 99%
“…A career goal has been described as a future position which an individual aspires to as part of his or her career and serves as a point of reference in the direction of one's career (Duxbury et al, 1999). The different needs of individuals are reflected in their attainment of different career goals (Counsell, 1996). A career goal can also clarify thinking, motivate and direct behaviour, and serve as a basis for the development of a career strategy (Greenhaus et al, 1995).…”
Section: Career Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Doherty, Viney, & Adamson (1997) noted that university students, especially those about to graduate, had not determined the course of their career and had a tendency to take whatever job was available. In a study conducted in England, Counsell (1996) demonstrated that when it came to determining a career path, families, close friends and the world views of the students had the greatest impact. However, students did not pay enough attention to the self-perceived skill level, competencies and needs pertaining to the job market.…”
Section: How University Students View the Issue Of Their Careersmentioning
confidence: 99%